Bibliometric Analysis of The Term “Marketing Sustainability” - Mohammad Gifari Sono (West Science Interdisciplinary Studies, 2023)
This study presents a bibliometric analysis of the term "marketing sustainability" to explore the growing trends, key contributors, and thematic focus in the academic literature. Marketing sustainability represents the integration of sustainable practices and principles into marketing strategies and activities, highlighting the growing importance of environmental, social, and economic considerations in contemporary marketing practices. This research examined 985 articles with themes related to marketing management. In the context of this study, we concluded that marketing management articles are classified into six clusters. The trend of marketing management research is more on the marketing side. There are several topics that frequently appear in publications, such as the marketing perspective of one variable on another. Topics such as Agrarian Sustainability and Sustainability Reporting have also not been researched much.